Evidence Based Public Health Practice: Brief Introduction - Marahatta, SB (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jmmihs.v1i2.9906 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(2) 2013; 38-40